Impacts of trade liberalization and market reforms on the rice sector in Sri Lanka - Weerahewa, Jeevika (International Food Policy Research Institute, 2004)
The overall objective of this research project is to assess the impacts of different types of government policies (pertaining to the domestic and external sectors) on the status of food security in the country, with particular emphasis on the paddy/rice sector....The study concludes by drawing policy implications, based on the analysis and findings of the study. Some of the important ones are that rice trade should be liberalized, as it leads to an increase in efficiency and net gains at the national level....A second policy implication is that government procurement should continue but private sector participation in imports should be allowed. Finally, the findings of this study indicate that methods to help farmers combat the oligopsony power of millers should be provided. These may include provision of storage and credit facilities and strengthening of farmer organizations.